Setting of the ~2560 Ma Qôrqut Granite Complex in the Archean crustal evolution of Southern West Greenland - Nutman, Allan P.; Friend, Clark R.L.; Hiess, Joe (American Journal of Science, 2011)
The Archean gneiss complex of West Greenland contains packages of unrelated rocks created during relatively short periods of time in arc-like magmatic environments, and having similarities to rocks formed at Phanerozoic convergent plate boundaries. The terranes of new Archean crust were amalgamated by collisional orogeny and then partitioned by post-assembly tectonic processes. Having summarized the origin of West Greenland Archean crust in arc-like environments, this paper then focuses on new data concerning the latest Neoarchean post terrane-assembly "intra-continental" tectonic and magmatic evolution of the region. Following the youngest documented high pressure metamorphism in a clockwise P-T-t loop at 2650 Ma, attributed to tectonic thickening of the crust, there is in West Greenland a 150 million year record of intermittent production of crustally-derived granite, shearing and folding under amphibolite facies conditions. This is exemplified by the SSW-NNE orientated Neoarchean Qôrqut Granite Complex (QGC) which forms a myriad of closely spaced coeval sheets NE of Nuuk town. SHRIMP U-Pb zircon dating of a homogeneous gray granite sheet gives a magmatic age of 2561±11 Ma, with 3800 to 3600 and 3070 to 2970 Ma zircon xenocrysts. The >40 km long Fjringehavn straight belt, a lower amphibolite-facies vertical shear zone, runs from the QGC's SE margin and contains strongly deformed granite sheets with a U-Pb zircon age of 2565±8 Ma but is cut by undeformed granite sheets dated at 2555±12 Ma. The >60 km long Ivisaartoq fault consisting of lowermost amphibolite-facies mylonite runs from the northwestern end of the main mass of granite. It formed post-2630 Ma, because granites of that age are truncated by it. Near the QGC's northeastern extent, 2559±3 Ma granitic lithons in a folded mylonite are cut by 2521±72 Ma granite sheets. At a deep structural level at the northern end of the QGC, deformed granitic neosomes give ages of 2567±9 and 2563±5 Ma. Therefore, at 2560 Ma, the ages within error for strongly ...